Best practice in the management of storage symptoms in male lower urinary tract symptoms: a review of the evidence base - Mauro Gacci (Therapeutic Advances in Urology, 2018)
Storage lower urinary tract symptoms (LUTS) are characterized by an altered bladder sensation, increased daytime frequency, nocturia, urgency and urgency incontinence. Some evidence underlines the role of metabolic factors, pelvic ischemia, prostatic chronic inflammation and associated comorbidities in the pathophysiology of storage LUTS. A detailed evaluation of the severity of storage LUTS, and the concomitance of these symptoms with voiding and postmicturition symptoms, is mandatory for improving the diagnosis and personalizing treatment. A detailed medical history with comorbidities and associated risk factors, a physical examination, a comprehensive analysis of all the features of LUTS, including their impact on quality of life, and a frequency–volume chart (FVC) or bladder diary, are recommended for men with storage LUTS. Several drugs are available for the treatment of LUTS secondary to benign prostatic obstruction (BPO). Alpha-blockers (α-blockers), 5-α-reductase inhibitors and phosphodiesterase type 5 inhibitors are commonly used to manage storage LUTS occurring with voiding symptoms associated with BPO. Muscarinic receptor antagonists and Beta 3-agonists (β3-agonists) alone, or in combination with α-blockers, represent the gold standard of treatment in men with predominant storage LUTS. There is no specific recommendation regarding the best treatment options for storage LUTS after prostatic surgery.